Finite Element Analysis of SS316L-Based Five-Hole Plate Implant For Fibula Reconstruction - Zakki Fuadi Emzain; AM. Mufarrih; Ratna Monasari; Fataa Kusumattaqiin; Rangga E. Santoso; Nanang Qosim (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
This study analyzed the design performance of SS316L-based plate implant for fibula restoration using a Finite Element Analysis approach. The simulated model design has dimensions of 35 x 5 x 1.5 mm and five holes with 2-3 configuration. The results of the bending test simulation showed that the values for both displacement and Von Mises stress that occurred (0.008 mm and 116 MPa of each) were still considerably below the yield stress of the SS316L material. The same results were also shown in the tensile test simulation, although the clamping setting on the plate was changed on the other side. From this finite element analysis approach, the SS316L-based five-hole plate implant design has a fairly good strength performance as a fibular bone-implant restoration product.